An immunohistochemical investigation of the expression of somatostatin receptor subtypes – should therapeutic trials be performed to determine the efficacy of somatostatin analogs in treating advanced thyroid malignances? - Pisarek, H.; Pawlikowski, M.; Marchlewska, M.; Minias, R.; Winczyk, K. (TumorDiagnostik & Therapie, 2015)
Somatostatin and its analogs through the specific receptor are known to demonstrate antiproliferative, anti-angiogenic and pro-apoptotic actions. The presence of SSTR-1–5 has not been sufficiently explored in poorly differentiated and undifferentiated thyroid tumors. The aim was to investigate the SSTR subtypes expression in these aggressive thyroid tumors. The study also discusses the usefulness of SSTR analogs as an alternative to conventional forms of therapy.Methods: The analysis was performed by immunohistochemistry on the 14 archived poorly differentiated and 4 anaplastic thyroid carcinomas. A group of benign thyroid pathologies consisting of 11 patients was also included.Results: SSTR-1, 2A, 2B, 3 and 5 were found to be expressed both in benign and malignant thyroid diseases, while SSTR-4 was not. Expression of SSTR-1 and SSTR-5 was found in samples with poorly differentiated thyroid tumors with a score of at least 2.0 being recorded in 10 tumors (71.4 %). For SSTR-2A the same or higher score was noted in 5/14 (35.7 %), for SSTR-2B in 4/14 (28.6 %) and for SSTR-3 in 3/14 (21.4 %) samples. SSTR-1, 2B and 5 were found to have a score of at least 2.0 in all undifferentiated thyroid tumors. Immunostaining of SSTR-2A and 3 was observed in 50 % of samples. The immunopositive reactions were observed both in the membranes and cytoplasm of the thyroid cancer’ cells. In some cases positive immunostaining was localized also in the endothelium of intrathyroidal blood vessels.Conclusions: The somatostatin multiligand analogs or selective agonists could be considered alternatives to conventional therapeutic agents in aggressive thyroid tumors.
Keywords: aggressive thyroid carcinomas; somatostatin receptor subtypes; treatment modality